Opening Up by Writing it Down : how expressive writing improves health and eases emotional pain - Pennebaker, James W., 1950-; Smyth, Joshua M., ....- (New York : The Guilford Press, 2016)
Expressing painful emotions is hard - yet it can actually improve our mental and physical health. This lucid, compassionate book has introduced tens of thousands of readers to expressive writing, a simple yet powerful self-help technique grounded in scientific research. Leading experts James W. Pennebaker and Joshua M. Smyth describe how taking just a few minutes te write about deeply felt personal experiences or problems may help you: heal old emotional wounds, feel a greater sense of well-being, decrease stress, improve relationships, boost your immune system. Vivid stories and examples yield compelling insights into secrets, self-disclosure, and the hidden price of silence. The third edition incorporates findings form hundreds of recent studies and includes practical exercices to help you try expressive writing for yourself. It features extensive new information on specific health benefits, as well as when the approach may not be helpfull.
Keywords: Narratieve psychologie